KEMANDIRIAN ANAK INTELLECTUAL DISABILITY TERKAIT DENGAN TINGKAT KEMATANGAN SOSIAL - Fadli, Muh Khoironi; Pamungkas, Dewi Retno; Sumiyarini, Retno (Universitas Jenderal Achmad Yani Yogyakarta, 2014)
Background: Intellectual disability is disorder of intellectual function that is significantly below average with various deficits in adaptive function, such as taking care of oneself or occupational activities that emerge before the age of 18 years old. One characteristic of intellectually disabled children in adaptive function is social maturity disorder. Children with intellectual disability have problem in social maturity and limitation in fulfilling needs in daily activities. Objective: To identify correlation between social maturity and self-reliance of children with intellectual disability. Methods: The study was non experimental. It used cross sectional design and quantitative approach. Samples were taken through proportionate stratified random sampling technique. Research instrument used to assess social maturity was Vineland Social Maturity Scale (VSMS) and self-reliance was Functional Independence Measure for Children (WeeFIM). Subject of the study were children with intellectual disability in SLB Bakti Siwi that met inclusion and exclusion criteria as many as 61 children. The study used non parametric Spearmanâs Rank Correlation test at significance p<0.05. Result: Social maturity was high in 9 children (14.8%), medium in 23 children (37.7%), and low in 29 children (47.9%). Self-reliance of children with intellectual disability showed average score (mean) 105.36 with deviation standard 15.43 and range 56-126. Score of correlation between social maturity and self-reliance of children with intellectual disability in SLB Bakti Siwi showed p value 0.000 (p<0.05). Conclusion: There was significant correlation between social maturity and sel-reliance of children with intellectual disability in SLB Bakti Siwi with score of correlation in strong category. Keywords: intellectual disability, social maturity, self-reliance